A new ratio with PaO2/FiO2 and pulmonary arterial systolic pressure in the prognosis of intermediate high risk pulmonary embolism. (14th October 2021) - Pires, M; Santos, J M; Neto, V; Correia, J; Ferreira, G; Costa Cabral, J; Almeida, I
Abstract: Background: Intermediate high (IH) risk pulmonary embolism (PE) defines a category of patients (P) at increased risk of haemodynamic decompensation. Therefore, it is important to develop tools to identify P who will have an unfavourable outcome. The ratio between arterial oxygen partial pressure (PaO2) to fractional inspired oxygen (FiO2) – P/F ratio - is associated with in-hospital mortality (IHM) in PE. Pulmonary arterial systolic pressure (PASP) is another prognostic factor, related with right ventricular (RV) pressure overload. This study evaluates the usefulness of a new ratio with P/F divided by PASP (P/F:PASP), reflecting both severity of respiratory failure and pressure overload, in the prognosis of P with IH risk PE. Methods: All P admitted for IH risk PE in an Intensive Cardiac Care Unit (ICCU) for 10 years were included. P/F ratio was calculated with admission blood gas analysis and PASP was obtained with echocardiography at admission in ICCU. P/F:PASP ratio was considered low if inferior to its median. Need for fibrinolysis and IHM were assessed. Follow-up (FU) of 2 years for all-cause mortality was done. Statistical analysis used chi-square and Mann-Whitney U tests, binary logistic regressions and Kaplan-Meier curves. Results: 101 P were studied (mean age 63±17 years; 35.6% male). Mean P/F, PASP and P/F:PSAP were 264±68, 45±15 mmHg and 6.7±3.3, respectively. P/F:PASP was considered low if inferior to 5.9. There was no difference in age, gender, comorbidities or Pulmonary Embolism Severity Index (PESI) between P with low or high P/F:PASP. However, low P/F:PASP ratio was associated with tachypnea at admission (p=0.034), higher BNP level (p=0.011), right precordial leads T-wave inversion (p=0.029), presence of echocardiographic right ventricle dilation (p=0.002) and lower TAPSE (p=0.002). Among P who underwent fibrinolysis, 60.4% had low P/F:PASP and 39.6% had high P/F:PASP ratio (χ 2 =3.32, p=0.05). P/F:PASP ratio was a predictor of fibrinolysis (OR 0.83, 95% CI 0.72–0.96, p=0.011), with lower ratio increasing the probability of fibrinolysis. This result was independent from PESI (OR 0.84, 95% CI 0.72–0.97, p=0.015). P/F:PASP ratio was also a predictor of IHM (OR 0.62, 95% CI 0.38–1, p=0.05). During FU, there was no difference in mortality between P with low or high P/F:PASP ratio (8.5% vs. 10.4%, respectively; Kaplan-Meier χ 2 =0.095; p=0.758). Conclusions: In IH risk PE, low P/F:PASP ratio was associated with analytical, electrocardiographic and echocardiographic risk features. In this study, P/F:PASP ratio was a predictor of short term prognosis, allowing identification of P at higher risk of fibrinolysis and IHM, but it was not useful for long term prognosis, as 2-year mortality was similar between the groups. Therefore, this ratio, as a measure of both respiratory failure and pressure overload, might allow refinement in risk stratification of P with IH risk PE. FUNDunding Acknowledgement: Type of funding sources: None.